2009
DOI: 10.1016/j.jcf.2008.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Common mutations in cuban cystic fibrosis patients

Abstract: So far, more than 1500 mutations have been reported in the cystic fibrosis transmembrane conductance regulator (CFTR) gene. Mutational spectrum varies in accordance with geographic and/or ethnic origin. In this study, we have analyzed seven common CF mutations (p.F508del, p.G542X, p.R1162X, p.N1303K, p.R334W, p.R553X and c.3120+1G>A) taking into account the ethnic origin of the Cuban population which is mainly influenced by Spanish and sub-Sahara African contribution. All but p.N1303K have been detected in our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…This variant is a prevalent CF causing mutation among CF patients of east Mediterranean countries such as Crete, Spain, France, Cuba and Mediterranean France (12)(13)(14)(15). Moreover, the variant c.1000C>T has been reported in Brazil, Latin America, Po-land, Greece, Romania, Germany, Czechs, and Ukraine (16)(17)(18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%
“…This variant is a prevalent CF causing mutation among CF patients of east Mediterranean countries such as Crete, Spain, France, Cuba and Mediterranean France (12)(13)(14)(15). Moreover, the variant c.1000C>T has been reported in Brazil, Latin America, Po-land, Greece, Romania, Germany, Czechs, and Ukraine (16)(17)(18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%
“…Karimi et al reported that the frequency of the c.1000 C>T mutation is as high as 40% in the CF patients from western Iran, whereas delF508 is observed only in 18% of their cases ( Karimi et al, 2018 ). It is suggested that this mutation has multiple unrelated origins ( Morral et al, 1994 ) and has been reported in distinct populations ( Estivill et al, 1997 ; des Georges et al, 2004 ; Chevalier-Porst et al, 1994 ; Collazo et al, 2009 ; Lay-Son et al, 2011 ), with a considerable incidence in Southern Europe and Latin America ( Pérez et al, 2007 ; Castellani et al, 2008 ). c.1000C>T is not a frequent mutation except in Brazilians (frequency of 2.64%) ( Pereira et al, 2019 ) and ethnic Russians (0.69%) ( Petrova et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The distribution of mutations appears to be specific to race and/or ethnic origin (Collazo et al, 2009), with the dominant ∆F508/∆F508 homozygous mutation accounting for 27% of the Italian CF population compared to at least 50% in Northern Europe and the United States (Bossi et al, 2004). There is no evidence of the ∆F508 mutation in the Japanese CF population (Yamashiro et al, 1997).…”
Section: Mutationsmentioning
confidence: 95%